Strength and conditioning considerations for mixed martial arts - Bounty, P.; Campbell, B.; Galvan, E.; Cooke, M.; Antonio, J. (Strength and Conditioning Journal, 2011)
Mixed martial arts (MMA) is an exciting and complex sport that combines th techniques of boxing, Muay Thai boxing, and various grappling disciplines such as Greco-Roman wrestling, freestyle wrestling, Brazilian Jiu-Jitsu. MMA is a physiologically demanding sport. It can potentially challenge and tax all of the energy systems and the possibility of verreaching/overtraining is a concern. To date, there is limited peer-rewied research examining the optimal training methods for an athlete competing in MMA. The purpose of this review is to discuss some of the available peer-reviewed research surrounding this sport and provide general considerations for the strength and conditioning specialists.